Intraspecific differentiation in genetic structure in Panicum coloratum L.: importance for germplasm conservation and breeding - Armando, Lorena Vanesa (2023)
Success in a breeding program is highly dependent on the information regarding genetic variability and its structure of the available germplasm. Particularly in poorly domesticated species, such information is generally scarce. Panicum coloratum L. is a warm-season perennial grass with potential to increase production in agricultural degraded areas. Its two varieties have high genetic polymorphism and morphological overlapping. The goal of the present study was to assess the genetic diversity and intraspecific structure of a collection of P. coloratum using ISSR molecular markers. Eight accessions of var. makarikariense Gooss. and ten from var. coloratum, plus two commercial materials were analyzed. Differences in variability between varieties were evident: polymorphism and percent of variety specific loci were lower (79%P and 10.3%) in var. makarikariense than in var. coloratum (93%P and 30.9%). Analysis of molecular variation (AMOVA) revealed 13.7% (p = 0.001) of variation was attributable to differences between varieties, and 43.8% remained within the accessions. Individuals of var. coloratum showed higher mean genetic distance among them than the ones of var. makarikariense. The PCO biplot and the dendrogram showed some distinction between varieties, although some accessions of var. coloratum were close to var. makarikariense. Variation in var. coloratum agreed with an allogamous reproductive behavior. Alternatively, less variable closely grouped individuals in var. makarikariense, concur with frequent vegetative reproduction by rhizomes of a reduced number of genotypes. Our study showed that genetic variation had different structure between varieties. This difference should be taken into account when planning germplasm management and conservation and in designing breeding programs.